2008
DOI: 10.1007/s10495-008-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Tax protein cooperates with Ras in protecting cells from apoptosis

Abstract: Tax protein of the human T-cell leukemia virus type 1 (HTLV-1) plays a critical role in HTLV-I-correlated diseases through its ability to deregulate the expression of a vast array of cellular genes. We have previously shown that Tax counteracts apoptosis induced by stimuli triggering mitochondria apoptotic pathway, most likely by activating CREB-mediated transcription and affecting the phosphorylation levels of CREB at Ser-133. Here, we report data that indicate the oncoprotein Ras as a possible mediator of Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…33,34 Recently, Ras-ERK signaling was shown to be particularly important for Taxmediated protection of cells from apoptosis. 35 Our study demonstrates that Roc can block the Ras-ERK signaling pathway and thereby downregulate c-FLIP expression through inhibition of eIF4E function, a key factor that controls the rate-limiting step of translation. 29 Although inhibition of eIF4E function will lead to inhibition of translation in general, only the expression levels of c-FLIP proteins were shown to be downregulated by Roc treatment.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…33,34 Recently, Ras-ERK signaling was shown to be particularly important for Taxmediated protection of cells from apoptosis. 35 Our study demonstrates that Roc can block the Ras-ERK signaling pathway and thereby downregulate c-FLIP expression through inhibition of eIF4E function, a key factor that controls the rate-limiting step of translation. 29 Although inhibition of eIF4E function will lead to inhibition of translation in general, only the expression levels of c-FLIP proteins were shown to be downregulated by Roc treatment.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, 100 nM of Roc-AR, which was shown to completely block 35 S-methionine incorporation (Figure 4b), showed no effect on protein synthesis in the rabbit reticulocyte cell-free system (Figure 4c). These data indicate that Roc does not directly inhibit the translation machinery, but rather acts through inhibition of the signaling pathway that is required for translation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent findings showed that iNOS expression promotes tumorigenesis in ER-negative breast cancer by a mechanism in which NO induces Snitrosylation of wild-type Ras, leading to phosphorylation and activation of the transcription factor Ets-1 through the Ras/MEK/ERK pathway [166]. Interestingly, the Ras protein has been shown to be involved in the survival of HTLV-1 infected cells [167,168]. Akt is another multifunctional regulatory protein that is also involved in cellular metabolism, proliferation and survival.…”
Section: Inos/no and S-nitrosylation Of Proteinsmentioning
confidence: 99%
“…In Tax-expressing cells, Tax modulates and increases the phosphorylation (activation) of Ras and ERK kinases, thus facilitating cell proliferation [46] . In this context, Tax protects from apoptosis cooperating with Ras in activating ERK signaling [47] . Furthermore, Tax physically interacts, through its PDZ binding motif, and blocks the function of Erbin, negative regulator of the Ras-Raf-ERK pathway, enhancing the cell proliferation and the protection from apoptosis [48] .…”
Section: Tcr Signalingmentioning
confidence: 99%